Re-visiting the occurrence of undeclared species in sausage products sold in Canada. (August 2019) - Shehata, Hanan R.; Naaum, Amanda M.; Chen, Shu; Murphy, Torie; Li, Jiping; Shannon, Kelly; Awmack, David; Locas, Annie; Hanner, Robert H.
Abstract: Meat and poultry are major protein sources for humans worldwide. Undeclared ingredients in processed meat products, like sausage, continue to be identified in retail products all over the world. In collaboration with the Canadian Food Inspection Agency, a previous study of products purchased in Canada showed 20% mislabelling rate in sausage meats when tested for beef, pork, chicken, turkey and horse using DNA barcoding and digital PCR. In a follow-up to this study, an additional 100 "single species" sausage products were collected from Canadian retail markets, one year after our earlier study, to determine the prevalence of undeclared meat species in sausage. A new hierarchy of complementary molecular methods was applied in this study, including the testing of new target species (sheep and goat), in addition to beef, pork, chicken, turkey and horse. First, all samples were tested using DNA barcoding using universal primers, which revealed that 97% of the samples contained the declared species, presumably as the predominant species. Second, all samples were tested using ddPCR assays specifically targeting beef, pork, chicken, and turkey, which revealed that five beef samples, three chicken samples and two turkey samples contained undeclared species. Additionally, ddPCR revealed the presence of undeclared sheep in five samples. Overall, using complementary molecular methods, 14% of the samples contained additional undeclared species. It was encouraging to find a reduced rate of mislabelling compared to the previous study, though it remains clear that meat mislabelling is still an issue affecting Canadian consumers. The results from this study can be used to support decision-making processes for future inspection and monitoring activities in order to control species substitution or adulteration to protect consumers. Graphical abstract: Unlabelled Image Highlights: Meat mislabelling was studied in 100 single species sausage products from Canada. Target species included beef, pork, chicken, turkey, horse, sheep and goat. 97% of the samples contained the declared species as the predominant species. 14% of the samples contained additional undeclared species. It remains clear that meat mislabelling is an issue affecting Canadian consumers.